2021
DOI: 10.1111/jfpp.16262
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and structure of starches of foxnut ( Euryale ferox Salisb.) from India and its application

Abstract: The physicochemical characteristics in terms of composition, pasting properties, in vitro starch digestibility, morphology, XRD, FT‐IR, and functional properties of starch, isolated from the kernels of Euryale ferox seed cultivated in Northeastern Region of India were studied and utilized them in formulation of bread. E. ferox kernel starch (EFKS) exhibited an A‐type diffraction pattern and granule sizes ranged from 1 to 3 μm in diameter and were polyhedral shape. EFKS exhibited high pasting temperature indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A strong negative correlation (R 2 : 0.82) between relative crystallinity and amylose content was observed. Previously, such negative correlation between relative crystallinity and amylose was inferred for gorgon nut starch by Devi & Deka (2022). It was reported that relative crystallinity of flour significantly influenced the functional characteristics, gelatinisation temperature, rheological and retrogradation behaviour of food materials (Singh et al, 2003;Jiang et al, 2012;Zhao et al, 2016).…”
Section: Structural Characteristics Of Rgnf Fractionsmentioning
confidence: 94%
“…A strong negative correlation (R 2 : 0.82) between relative crystallinity and amylose content was observed. Previously, such negative correlation between relative crystallinity and amylose was inferred for gorgon nut starch by Devi & Deka (2022). It was reported that relative crystallinity of flour significantly influenced the functional characteristics, gelatinisation temperature, rheological and retrogradation behaviour of food materials (Singh et al, 2003;Jiang et al, 2012;Zhao et al, 2016).…”
Section: Structural Characteristics Of Rgnf Fractionsmentioning
confidence: 94%
“…Cereal starches are bimodal, so one needs to separate starch granules into two fractions. The botanical origin, weather conditions and environmental factors, farming techniques, and procedure used for starch isolation can all influence its chemical composition and structure [16].…”
Section: Isolation Of Starchmentioning
confidence: 99%
“…It is highly nutritious with an amino acid index of about 89–93%, among them, the amount of glutamic acid, leucine, and isoleucine is about 16.64%, 8.34%, and 4.18%, respectively, whereas arginine+lysine/proline ratio is 4.74–7.6 (Jana & Idris, 2018). Various researchers reported the presence of trace elements in E. ferox such as Cu (0.3–0.71 mg/kg), Zn (0.9–1.50 mg/kg), Fe (0.8–5.73 mg/kg), and Mn (11.3–13.83 mg/kg) (Devi & Deka, 2021; Kumar, Singh, & Bhatt, 2016; Kumar, Yadav, et al, 2016).…”
Section: Nutritional Profile Of E Feroxmentioning
confidence: 99%
“…The seeds of E. ferox germinate within the water and during the germination stages, the protein content of the seed increases as it ages (Khadatkar, Mehta, & Gite, 2020). E. ferox is an organic non–cereal food, which is highly nutritious and is utilized as a dry fruit due to its high carbohydrates (80% starch), mineral, protein, and low‐fat content (Devi et al, 2020; Devi & Deka, 2021; Jana & Idris, 2018; Kumar, Singh, & Bhatt, 2016; Kumar, Yadav, Paras, Nath, & Kumari, 2016; Singh et al, 2017). It is considered a superfood in terms of various health benefits such as cardioprotective, antidiabetic, antioxidant, antifatigue, etc.…”
Section: Introductionmentioning
confidence: 99%